1995
DOI: 10.1159/000239381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Desferrioxamine on Cisplatin-induced Nephrotoxicity in Normal Rats

Abstract: Biochemical and histological evaluations of the effects of the iron chelator desferrioxamine on the nephrotoxicity induced by cisplatin in normal rats were carried out. A single dose of cisplatin (7.5 mg/kg, intravenously) caused nephrotoxicity that manifested biochemically as an elevation of blood urea nitrogen, serum creatinine and an increase in the kidney weight as a percent of body weight. Moreover, severe decreases in serum calcium and albumin were observed. Histopathological examination of kidney tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 18 publications
4
4
0
Order By: Relevance
“…This imbalance between pro‐oxidants and anti‐oxidants, in favour of the former, causes the formation of oxidative stress (reactive oxygen species and free radicals) in kidney tissues. Thus, the observed increase in the levels of NO x and TBARS in kidney tissues in the present study is consistent with results of previous studies, which have demonstrated the involvement of oxidative stress, lipid peroxidation and mitochondrial dysfunction in CDDP‐induced nephrotoxicity 45–48 …”
Section: Discussionsupporting
confidence: 93%
“…This imbalance between pro‐oxidants and anti‐oxidants, in favour of the former, causes the formation of oxidative stress (reactive oxygen species and free radicals) in kidney tissues. Thus, the observed increase in the levels of NO x and TBARS in kidney tissues in the present study is consistent with results of previous studies, which have demonstrated the involvement of oxidative stress, lipid peroxidation and mitochondrial dysfunction in CDDP‐induced nephrotoxicity 45–48 …”
Section: Discussionsupporting
confidence: 93%
“…This speculation agreed with previous studies which have demonstrated the involvement of oxidative stress, lipid peroxidation, and mitochondrial dysfunction in cisplatin-induced nephrotoxicity [29, 30, 34, 35]. The contribution of NO to the cytotoxicity and organ toxicity of anticancer drugs has been previously reported [36, 37, 38].…”
Section: Discussionsupporting
confidence: 92%
“…Based on enhanced lipid peroxidation induced by cisplatin, lipid peroxidation is considered another iron‐related mechanism that is important in cisplatin nephrotoxicity . The protective effects of hydroxyl radical scavengers and iron chelators in several in‐vitro and in‐vivo models of cisplatin‐induced renal failure have been largely taken as a reason for the iron‐mediated hydroxyl radical generation in tissue damage …”
Section: Discussionsupporting
confidence: 82%
“…The possible involvement of iron in cisplatin‐induced nephrotoxicity became evident from studies in which iron chelators (2,3‐dihydroxybenzoic acid or deferoxamine) were shown to be renal protective . However, as far as we know, the effect of deferiprone on cisplatin‐induced nephrotoxicity remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%